Field and lab convergence in poissin LUPI games - Robert Östling; Joseph Tao-yi Wang; Eileen Chou; Colin F. Camerer (Stockholm School of Economics, The Economic Research Institute (EFI), 2007)
Game theory is usually difficult to test precisely in the field because predictions typically depend sensitively on features that are not controlled or observed. We conduct one such test using field data from the Swedish lowest unique positive integer (LUPI) game. In the LUPI game, players pick positive integers and whoever chose the lowest unique number wins a fixed prize. Theoretical equilibrium predictions are derived assuming Poisson-distributed uncertainty about the number of players, and tested using both field and laboratory data. The field and lab data show similar patterns. Despite various deviations from equilibrium, there is a surprising degree of convergence toward equilibrium. Some of the deviations from equilibrium can be rationalized by a cognitive hierarchy model.
Keywords: C72; C92; C93; L83; 330; Population uncertainty; Poisson game; guessing game; experimental methods; behavioral game theory; level-k; cognitive hierarchy; Spieltheorie; Test; Verhalten; Schweden